The Impact of Oil Revenue Shocks on the Volatility of Iran’s Stock Market Return - Davoudi, Sina; Fazlzadeh, Alireza; Fallahi, Firouz; Asgharpour, Hossein (International Journal of Energy Economics and Policy, 2018)
The aim of this study was to examine the impact of oil revenue shocks on the volatility of Tehran’s stock market return, by applying GARCH (Generalized Auto Regressive Conditional Heteroscedasticity) model with seasonal data from January 1993 to March 2014. After calculating the volatility stock returns via GARCH models, we employed ARDL (Auto Regressive Distributed Lag) model to estimate the oil shocks effects. The population is consisted of all active companies in Tehran’s stock market during the period of this research. Study results showed that oil shocks are associated with positive effects on the stock market volatility, representing that this shocks are one of the main motivators of stock price index growth in Iran’s case. More ever, exchange rate and liquidity had same effects on the stock market return through increasing the volatility. On the other hand our results indicated that there were no relations between consumer price index and stock market volatility. Other result of this study refers to effects of sanctions imposed by the US and Europe, which elicits the increase of stock market volatility from the day they have been taken place. Keywords: Oil revenue, stock market returns volatility, sanctions, exchange rate, consumer price index, portfolio management. JEL Classifications: M21, G11, E10